2012
DOI: 10.1179/1743289811y.0000000031
|View full text |Cite
|
Sign up to set email alerts
|

Observations on interphase characterisation in polymer composites by nanoscale indentation and use of AFM cantilever torsion to identify measurement artefacts

Abstract: SUMMARYThe results presented in this paper explore the extent to which indentation in the interfacial region of polymer composites can be used to identify, unambiguously, an interphase of distinct elastic properties. Supporting evidence is presented in the form of AFM-indentation in the interfacial region of two polymer composites, a glass fibre-reinforced vinylester and a glass flake-reinforced polypropylene, where a transition region of measurement artefact is revealed as opposed to a physically distinct int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Hodzic et al [4] found the interphase to have a higher stiffness than the surrounding matrix, which it was argued was a consequence of the coupling agent dispersing into the matrix after water ageing. Recent work [7] has shown that whilst a region of higher stiffness can be measured, its extent is much more limited (approximately 200 nm) and the torsion of the indenter tip is dominated by the fibre reinforcement. The surface was prepared for AFM analysis using a modified version of the mechanical polishing method employed by Khanna et al [8] with additional ultrasonic bath treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hodzic et al [4] found the interphase to have a higher stiffness than the surrounding matrix, which it was argued was a consequence of the coupling agent dispersing into the matrix after water ageing. Recent work [7] has shown that whilst a region of higher stiffness can be measured, its extent is much more limited (approximately 200 nm) and the torsion of the indenter tip is dominated by the fibre reinforcement. The surface was prepared for AFM analysis using a modified version of the mechanical polishing method employed by Khanna et al [8] with additional ultrasonic bath treatment.…”
Section: Methodsmentioning
confidence: 99%
“…During indentation, the torsion of the cantilever was recorded using a LabVIEW (National Instruments, Texas, USA) interface as in [7]. The LabVIEW detection system measured the voltage difference of the photosensitive diode which relates principally to the torsion of the cantilever and lateral force on the indenter tip".…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the arrangement of basal planes, predominant configurations are circumferential and radial, but in the core of the fiber, alignment is undetectable, and consequently it is considered as transversely isotropic. [49][50][51][52][53] In 3D composites reinforced with this type of fibers, the effective mechanical properties will be affected by the fibers. The current analytical models and numerical data available are not adequate because they assume that the fiber is totally isotropic and homogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the arrangement of basal planes, predominant configurations are circumferential and radial, but in the core of the fiber, the alignment is undetectable, and consequently it is considered as transversely isotropic. [40][41][42][43][44] In composites reinforced with this type of fibers, the effective mechanical properties will be affected by the fiber, the interphase between the fiber and the matrix. The analytical models and nanoindentation data available are not adequate because they assume that the fiber is totally isotropic and homogeneous.…”
Section: Introductionmentioning
confidence: 99%